Towards standardisation and improved understanding of sleep restriction therapy for insomnia disorder: A systematic examination of CBT-I trial content. (October 2015) - Kyle, Simon D.; Aquino, Maria Raisa Jessica; Miller, Christopher B.; Henry, Alasdair L.; Crawford, Megan R.; Espie, Colin A.; Spielman, Arthur J.
Summary: Sleep restriction therapy is a core element of contemporary cognitive-behavioural therapy for insomnia and is also effective as a single-component therapeutic strategy. Since its original description, sleep restriction therapy has been applied in several different ways, potentially limiting understanding of key therapeutic ingredients, mode of action, evidence synthesis, and clinical implementation. We sought to examine the quality of reporting and variability in the application of sleep restriction therapy within the context of insomnia intervention trials. Systematic literature searches revealed 88 trials of cognitive-behavioural therapy/sleep restriction therapy that met pre-defined inclusion/exclusion criteria. All papers were coded in relation to their description of sleep restriction therapy procedures. Findings indicate that a large proportion of papers (39%) do not report any details regarding sleep restriction therapy parameters and, for those papers that do, variability in implementation is present at every level (sleep window generation, minimum time-in-bed, sleep efficiency titration criteria, and positioning of sleep window). Only 7% of papers reported all parameters of sleep restriction treatment. Poor reporting and variability in the application of sleep restriction therapy may hinder progress in relation to evidence synthesis, specification of mechanistic components, and refinement of therapeutic procedures for patient benefit. We set out guidelines for the reporting of sleep restriction therapy as well as a research agenda aimed at advancing understanding of sleep restriction therapy.